L’importation de tuiles anglaises du Somerset en Bretagne au xixe siècle : un réexamen après 40 ans de recherches - Michael Batt (Archéologie Médiévale)
Fieldwork carried out in the early 1980s confirmed that large quantities of tiles, mainly manufactured by Colthurst, Symons & Co Ltd, in Bridgwater (Somerset, England), were imported into northern Brittany during the second half of the nineteenth and early twentieth century. These roof-tiles, situated chronologically between the use of thatch and the now ubiquitous slate, testify a cross-channel trade of goods that has also left some evidence in the archives. Following these observations during the 1980s concerning the presence of English tiles in Brittany, it seemed important to publish the results of this first field investigation. 40 years later, a review appeared to be necessary, and especially since examples remaining in place are becoming scarce: this article revisits the evidence while providing updates, unpublished information from additional research at the Côtes d'Armor archive office in Saint Brieuc, announcements in the local press and new bibliographical references. Further information concerning the port of Bridgwater and the functioning of different brick and tile manufacturers was provided by the Somerset Brick and Tile Museum. The author is indebted to Brian Murless of the Somerset Industrial Archaeology Society, members of the Bridgwater and District Archaeology Society, to Graeme Kirkham of Cornwall Archaeological Society for research into the manufacturer Colthurst, Symons & Co, and to Jean-Claude Fossey of the CRAHAM for updates to figures 1 and 2.